Formulasi NLC-Stick Ekstrak Bunga Telang (Clitoria ternatea L.) Dengan Variasi Konsentrasi Shea Butter dan Asam Stearat - Damanik, Virna Helena; Pratiwi, Liza; Wijianto, Bambang (Indonesian Journal of Pharmaceutical and Clinical Research, 2024)
NLC of telang flower extract has an effect as a sunscreen to protect the skin from sunlight. Stick preparation in NLC formulation can facilitate the use of sunscreen. This study aims to determine and compare variations in the concentration of Shea Butter (as a Base) and stearic acid (as a Harding Agent) and obtain the results of physical evaluation of variations in the concentration of Shea butter and Stearic Acid. NLCs of telang flower extract were formulated into formulas with varying concentrations of shea butter and stearic acid in the ratio of 80:20; 50:50; 20:80. Furthermore, the physical properties of NLC-Stick of bay flower extract were evaluated, including organoleptic test, homogeneity test, pH test, melting time test, and spreadability test. The results showed that the optimal variation of shea butter and stearic acid concentration was 50:50. The optimum formula of NLC-Stick of telang flower extract has a colour like the active substance, solid shape, soft aroma, homogeneous, pH of 4.56 Â± 0.3, melting time test of 21 minutes, and spreadability test of 3 cm. NLC-Stick with varying concentrations of shea butter:stearic acid (50:50) has a physical evaluation that meets the stick requirements.